Manajemen Mutu Terpadu Pendidikan Islam Dalam Prespektif Manal Hani - Kusharyati, Indah; Muhlis, Achmad (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
The quality management of Islamic education plays a strategic role in shaping a generation that excels intellectually, morally, and spiritually. From Manal Hani's perspective, this management approach integrates Islamic values with modern management principles to achieve the ultimate goal: producing insan kamil (perfect individuals). Through a library research method, this study examines three core principles in Manal Hani’s framework: tawhid as the foundation, the integration of science and religion, and continuous improvement (islah wa tajdid). The implementation of this concept includes applying Total Quality Management (TQM) based on Islamic values, enhancing teacher competence, developing a curriculum integrated with Islamic principles, utilizing technology, and conducting moral-based evaluations. The findings indicate that Manal Hani’s approach provides a strong foundation for high-quality Islamic education that remains relevant to contemporary needs while preserving its Islamic identity.